Heart failure reversal by ventricular unloading in patients with chronic cardiomyopathy: criteria for weaning from ventricular assist devices - Dandel, Michael (Oxford University Press, 2011)
AIMS: Unloading-promoted reversal of heart failure (HF) allows long-term transplant-free outcome after ventricular assist device (VAD) removal. However, because few patients with chronic cardiomyopathy (CCM) were weaned from VADs (the majority only recently), the reliability of criteria used for weaning decisions to predict long-term post-weaning success is barely known. After 15 years of weaning experience, we assessed this issue. METHODS AND RESULTS: In 47 patients with CCM as the underlying cause for HF, who were part of a total of 90 patients weaned from bridge-to-transplant-designed VADs since 1995, we analysed data on cardiac morphology and function collected before VAD implantation, echocardiographic parameters recorded during ‘off-pump’ trials, duration of HF before implantation, and stability of recovery before and early after VAD removal. Post-weaning 5 year freedom from HF recurrence reached 66%. Only five patients (10.6%) died due to HF recurrence or weaning-related complications. Pre-explantation off-pump left ventricular ejection fraction (LVEF) of ≥50 and ≥45% revealed predictive values for cardiac stability lasting ≥5 years after VAD removal of 91.7 and 79.1%, respectively. With each unit of LVEF reduction, the risk of HF recurrence became 1.5 times higher. The predictive value of LVEF ≥45% also became >90% if additional parameters like pre-explantation LV size and geometry, stability of unloading-induced cardiac improvement before VAD removal, and HF duration before VAD implantation were also considered. Definite cut-off values for certain parameters (including tissue-Doppler-derived LV wall motion velocity) allowed formulation of weaning criteria with high predictability for post-weaning stability, also in patients with incomplete cardiac recovery. CONCLUSIONS: Ventricular assist device removal in CCM patients is feasible and can be successful even after incomplete cardiac recovery. Parameters of pre-explantation cardiac function, LV size and geometry, their stability during final off-pump trials, and HF duration allow detection of patients with the potential to remain stable for >5 post-weaning years.